2021
DOI: 10.2991/assehr.k.210202.092
|View full text |Cite
|
Sign up to set email alerts
|

Perceived Satisfaction and Perceived Usefulness of E- Learning: The Role of Interactive Learning and Social Influence

Abstract: Understanding the factors that influence the satisfaction of e-learning is critical. Therefore, this study aims to investigate the relationship between interactive learning, social influence, and perceived usefulness on perceived satisfaction with e-learning. Seventy-three students taking online learning were surveyed using a questionnaire. The results of the structural equation modelling analysis show that interactive learning and perceived usefulness have a significant effect on e-learning perceived satisfac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
8
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 17 publications
5
8
1
Order By: Relevance
“…It also supports Liaw & Huang (2013) that student satisfaction, perceived usefulness, and interactive learning environments were statistically significant predictors of perceived self-regulation in e-learning environments by adopting smart technology in education. Moreover, this study confirmed by Amsal et al (2021) that student satisfaction with e-learning is significantly influenced by interactive learning and perceived usefulness. The finding supports the study of OSMAN, CHOO & Rahmat (2013) that perceived usefulness substantially influences intentions concerning computer use.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…It also supports Liaw & Huang (2013) that student satisfaction, perceived usefulness, and interactive learning environments were statistically significant predictors of perceived self-regulation in e-learning environments by adopting smart technology in education. Moreover, this study confirmed by Amsal et al (2021) that student satisfaction with e-learning is significantly influenced by interactive learning and perceived usefulness. The finding supports the study of OSMAN, CHOO & Rahmat (2013) that perceived usefulness substantially influences intentions concerning computer use.…”
Section: Discussionsupporting
confidence: 79%
“…Student satisfaction, perceived usefulness, and interactive learning environments were all found to be statistically significant predictors of perceived self-regulation in e-learning environments (Liaw & Huang, 2013). Interactive learning and perceived utility significantly impact the perceived satisfaction with e-learning (Amsal et al, 2021). Perceived usefulness has a significant impact on attitudes and intentions regarding computer use.…”
Section: Research Hypothesesmentioning
confidence: 92%
“…H1: Social influence has a positive effect on perceived ease of use. Amsal et al (2021) research on e-learning shows that peer influence will increase individuals' perceptions of the system's benefits and vice versa. Previous research has shown that social influence positively influences perceived usefulness (Lwoga & Lwoga, 2017;Min et al, 2019;Nikou & Economides, 2017;Sathye et al, 2018;Wu & Chen, 2017).…”
Section: Relationship Of Social Influence and Perceived Ease Of Usementioning
confidence: 99%
“…The research of (Chen et al, 2020) also succeeded in proving one of the hypotheses they developed, namely that interaction quality of an e-learning platform has a positive and significant influence on user satisfaction. Meanwhile, (Amsal et al, 2021) described the interactive learning environment through communication and exploration of activities aspects, and found that interaction factor has an influence on perceived satisfaction.…”
Section: Relationship Between Interaction and Perceived Satisfaction ...mentioning
confidence: 99%
“…Several studies have also proven a relationship between interaction and perceived satisfaction (Chen et al, 2020); (Baber, 2020); (Goh et al, 2017); (Azainil et al, 2019); (Amsal et al, 2021), as well as with perceived usefulness (Sher (2009, in (Azainil et al, 2019; (Abdullah et al, 2017); (Amsal et al, 2021); (Alhumaid et al, 2020). In addition to the interaction factor, learner characteristic is widely considered as a determining factor for the success or failure of an e-learning.…”
mentioning
confidence: 96%